Annual Growth of Individual Pension Funds and Progressive Analysis of It's Development in Turkey - Yüce, Enes (Zenodo, 2021)
States have established various social security systems in order to eliminate the risks that their citizens will face at various times. Over time, the existing social security systems not meeting the expectations sufficiently and the search for new funding sources in order to meet the financing needs of the states gave birth to the private pension system. Thus, through these funds, individuals were directed to save and additional income was provided to individuals during their retirement. On the other hand, it contributed to the development of economic resources and capital markets needed by states and to channel savings to investment. Private pension funds, which are considered very important by developed and developing countries and are valuable in terms of providing economic resources, are a type of investment. The Private Pension System Law, which began de facto on October 27, 2003, entered into force on October 7, 2001. While in some countries access to the pension system is left to the choice of individuals, in some countries this is subject to a legal requirement. The aim of this study is; To examine the size of the private pension funds over the last ten years and the number of participants included in the system, using data from the Pension Monitoring Center.